Law Strength of Notary Deed in Legality Strengthening Of the BUMDes in Perspective of Permendesa No.4 Of 2015 (Studies on Village-Owned Enterprises of Semarang) - Medina Praba Andini; Hari Condro Wibisono; Achmad Sulchan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study were 1) Aim and analyze the legal force of Deed in strengthening the legality of the establishment of village-owned enterprises be seen in the perspective of PERMENDESA No. 4 of 2015 (Studies in the village-owned enterprises of Semarang), 2) Aim and analyze the weaknesses and solutions Deed in the preparation of the establishment of village-owned enterprises in Semarang.The approach used in this study is a sociological juridical approach, sociological juridical approach is to identify and conceptualize law as a social institution that is real and functional in a real life system. Specifications research used in this study is descriptive analytical, analytical descriptive study sought to describe the legal issues, the legal system and to study it or analyze it according to the needs of the research in question.Based on the results of data analysis concluded that: 1) BUMDes established by Regulation village formed by the village government and village Permusyawatan Board by consensus together. In addition to the legitimacy of the establishment of Village Regulations as BUMDes, reality on the ground there are some BUMDes in Semarang which have included Deed in strengthening the legality of the establishment. Deed as reinforcement of legality establishment BUMDes have binding legal force that can provide legal certainty and legal protection in the future, 2) weaknesses in the establishment Deed preparation BUMDes based research are: 1. Each BUMDes will have the format of AD / ART different and certainly not the same as the standard format of a Notary Public. 2. References are minimal regarding creation BUMDes Deed of Establishment. Because in PERMENDESA No. 4 of 2015 only confirmed that each village can form BUMDes under Regulation village. Recording BUMDes establishment in the Deed is an initiative of the board BUMDes itself. The solution of these weaknesses is the knowledge and experience related notary deed BUMDes. Associated with the solution that has been mentioned in addition to the importance of the knowledge and experience of a Notary in making a deed, but also Notaries need to provide clarification of the law, the deed was made since the implementation of the duty office of Notary